Effect of Salvia sclarea L. extract on growth performance, antioxidant capacity, and immune function in lambs - Ma, Xiaoling; Niu, Yujie; Nan, Shanshan; Zhang, Wenju (Frontiers in Veterinary Science, 2024)
The aim of this experiment is to explore the effects of salvia sclarea extract on the growth performance, apparent nutrient digestibility, antioxidant capacity, and immune function of lambs. Sixty female lambs (Chinese Merino sheep) aged 2 months and weighing 20 ± 2 kg were selected and randomly divided into five groups of twelve lambs in each. While the control group (CK) received only basal feed, the experimental group was supplemented with different concentrations of salvia sclarea extract in the basal feed at 0.04 mL/kg (group CL1), 0.08 mL/kg (group CL2), 0.12 mL/kg (group CL3), and 0.16 mL/kg (group CL4). The feeding period was 85 days, including 15 days of pre-feeding and 70 days of regular feeding. Body weight and feed intake were recorded during the test period, and blood was collected at the end of the test for the determination of immune and antioxidant indices. The results showed that the average daily gain and average daily feed intake of lambs were significantly increased in CL3 group compared to CK group (p < 0.05). Also, the apparent nutrient digestibility of crude protein and neutral detergent fiber was significantly increased (p < 0.05). The Dry matter, acid detergent fiber and Ether extract were not significantly different (p > 0.05). The serum levels of superoxide dismutase, catalase, glutathione peroxidase, and antioxidant capacity were significantly higher in the CL2, CL3, and CL4 groups compared to CK group, while malondialdehyde levels were significantly lower (p < 0.05). The serum levels of immune globulin A, immune globulin G, immune globulin M, interferon-γ, and interleukin-10 were significantly higher and the levels of tumor necrosis factor-α and interleukin-1β were significantly lower in the CL2, CL3, and CL4 groups (p < 0.05). In conclusion, the addition of salvia sclarea extract to the ration promotes growth performance and nutrient digestion in lambs. Improvement of immune response by increasing immunoglobulin and cytokine concentrations. And it enhances the antioxidant status by increasing the antioxidant enzyme activity in lambs. Introduction This study aimed to explore the effects of Salvia sclarea extract on the growth performance, apparent nutrient digestibility, antioxidant capacity, and immune function of the lambs. Methods Sixty female lambs (Chinese Merino sheep) aged 2 months and weighing 20 ± 2 kg were selected and randomly divided into five groups of 12 lambs each. The control group (CK) received only basal feed, whereas the experimental group was supplemented with different concentrations of salvia sclarea extract in the basal feed at 0.04, 0.08, 0.12, and 0.16 mL/kg (CL1, CL2, CL3, and CL4, respectively). The feeding period was 85 days, including 15 days of pre-feeding and 70 days of regular feeding. Body weight and feed intake were recorded during the test period, and blood was collected at the end of the test to determine immune and antioxidant indices. Results The results showed that the average daily weight gain and feed intake of the lambs were significantly higher in the CL3 group than in the CK group (p < 0.05). In addition, the apparent nutrient digestibility of crude protein and neutral detergent fiber increased significantly (p < 0.05). The dry matter, acid detergent fiber, and ether extract were not significantly different (p > 0.05). Serum levels of superoxide dismutase, catalase, and glutathione peroxidase and antioxidant capacity were significantly higher in the CL2, CL3, and CL4 groups than in the CK group, whereas malondialdehyde levels were significantly lower (p < 0.05). The serum levels of immune globulin immune globulin A, immune globulin G, immune globulin M, interferon-γ, and interleukin-10 were significantly higher and the levels of tumor necrosis factor-α and interleukin-1β were significantly lower in the CL2, CL3, and CL4 groups (p < 0.05). Discussion In conclusion, the addition of the S. sclarea extract to the diet promoted growth performance and nutrient digestion in lambs. Immune response was improved by increasing Ig and cytokine concentrations. It enhances antioxidant status by increasing antioxidant enzyme activity in lambs.